Enhancing Pediatric Nursing Skills by Top Learning Strategies: Meningkatkan Keterampilan Keperawatan Anak dengan Strategi Pembelajaran Terbaik - Ayat A. Hameed, MScN; Adraa H. Shawq, PhD (Universitas Muhammadiyah Sidoarjo, 2024)
Background: The efficacy of educational strategies is crucial for nursing students to competently perform pediatric procedures like nasogastric tube insertion. Specific Background: This study evaluates the effectiveness of simulation, blended, and self-directed learning strategies in enhancing these skills among nursing students. Knowledge Gap: Previous research lacks a comprehensive comparison of these strategies' impacts on skill development in pediatric nursing contexts. Aims: The study aims to assess the effectiveness of different educational strategies on nursing students' ability to perform pediatric nasogastric tube insertions. Methods: A pre-experimental design was employed at the College of Nursing, University of Baghdad, involving 60 students divided into three groups. Data were collected via an observational checklist from October to December 2023 and analyzed using SPSS. Results: Significant improvements in students' skills were observed across all groups. Simulation strategy showed highly significant differences with p-values of .001 and large effect sizes (Partial Eta Squared: .887, .902, .582). Blended strategy also demonstrated significant results with p-values of .001 and large effect sizes (Partial Eta Squared: .813, .936, .883). The self-directed strategy was similarly effective, with p-values of .001 and large effect sizes (Partial Eta Squared: .871, .739, .667). Descriptive statistics revealed a notable increase in mean scores in post-tests, indicating the effectiveness of these strategies. Novelty: This study uniquely compares the effectiveness of simulation, blended, and self-directed learning strategies, providing comprehensive insights into their impacts on pediatric nursing education. Implications: The findings underscore the importance of incorporating diverse learning strategies in nursing curricula to enhance practical skills, suggesting that a combination of these methods could be most beneficial for student learning and competence in clinical settings. Highlights: Effective Strategies: Simulation, blended, and self-directed learning enhance pediatric nursing skills. Significant Improvement: All methods showed highly significant skill development with large effect sizes. Unique Comparison: The study provides valuable insights for nursing education curricula. Keywords: Nursing education, pediatric skills, nasogastric tube insertion, simulation learning, blended learning